The Effect of Rigid Inclusions on the Dynamic Response of Highway Embankment - Bouabdallah, Faris; Goudjil, Kamel; Messast, Salah (Engineering, Technology & Applied Science Research, 2023)
Soft soils are widespread in many areas of the East-West highway of Algeria, covering large areas. Construction projects such as highway embankments, airfields, roads, and railways in such areas experience several problems due to their low strength and permeability. This study used a fully dynamic analysis to evaluate the dynamic response of a highway embankment. The numerical analysis was carried out using the FLAC 2D version 8.10 software. The main objective was to evaluate the effect of rigid inclusions on the dynamic response of highway embankments by monitoring settlement, shear-strain curves, and maximum soil accelerations and displacements at different depth points. The obtained results showed that the configuration of the rigid inclusions significantly influences the dynamic response of the model. For instance, the settlement at 0.9m is 16% higher than at 0.2m from rigid inclusion.